2019
DOI: 10.1371/journal.pone.0211565
|View full text |Cite
|
Sign up to set email alerts
|

Energy partitioning in cattle fed diets based on tropical forage with the inclusion of antibiotic additives

Abstract: The aim of this study was to describe energy partitioning in dairy crossbreed bulls fed tropical forage-based diets supplemented with different additives. Twenty F1 crossbred bulls (Holstein x Gyr) with initial and final live weight (LW) averages of 190 ± 17 and 275 ± 20 kg were fed sorghum ( Sorghum bicolour ) and Tanzania grass ( Panicum maximum cv. Tanzania) silage (70:30 DM basis) with supplemented concentrate at a forage to concentrate ratio of 50:50. The bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…The study represents fecal energy loss of 32-35% GE intake (Table 4; calculated), which corroborates with the findings of da Fonseca et al (2019), who reported about 33.6% fecal GE loss in bulls fed with tropical forages. The estimated urinary energy loss represents 3.9-4.0% of GE intake ( IPCC (2019).…”
Section: Metabolism Of Nutrientssupporting
confidence: 90%
“…The study represents fecal energy loss of 32-35% GE intake (Table 4; calculated), which corroborates with the findings of da Fonseca et al (2019), who reported about 33.6% fecal GE loss in bulls fed with tropical forages. The estimated urinary energy loss represents 3.9-4.0% of GE intake ( IPCC (2019).…”
Section: Metabolism Of Nutrientssupporting
confidence: 90%
“…However, when adjusted for dose, bulls fed a diet with VIR presented greater average daily gain than those fed MON without affecting feed intake or feed conversion ratio. Other studies [ 19 , 20 ] verified that feed intake and total tract digestibility were not affected by supplementation with MON, VIR or both. Moreover, according to Fonseca et al [ 19 ] there were no differences in average daily gain or feed efficiency for bulls fed diets with MON, VIR, or both.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies [ 19 , 20 ] verified that feed intake and total tract digestibility were not affected by supplementation with MON, VIR or both. Moreover, according to Fonseca et al [ 19 ] there were no differences in average daily gain or feed efficiency for bulls fed diets with MON, VIR, or both. Consequently, the inclusion of MV during the whole feedlot period may not justify the costs of its adoption.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Out of 41 papers, 17 articles were excluded for the following reasons: summary papers (4), no CH 4 emission measurements (2), no monensin/treatment effect results reported (2), without control measurements (3), conference papers as there were duplicate publications of the similar study (2), conference paper only reported an abstract, simulation papers (2), and paper that investigated the effects of monensin when mixed with other feed additives. The final database had a total of 24 papers that met the criteria and remained in the database; however, 13 were related to beef cattle [ 29 , 36 , 38 , 39 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and 11 were related to dairy cattle [ 8 , 9 , 28 , 30 , 31 , 32 , 33 , 34 , 53 , 54 , 55 ]. Then, beef cattle papers were excluded from the database.…”
Section: Methodsmentioning
confidence: 99%